2006
DOI: 10.1111/j.0014-3820.2006.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Ants Enhance Diversification in Lycaenid Butterflies? Phylogeographic Evidence From a Model Myrmecophile, Jalmenus Evagoras

Abstract: Abstract. The ant-tended Australian butterfly, Jalmenus evagoras, has been a model system for studying the ecology and evolution of mutualism. A phylogeographic analysis of mitochondrial DNA cytochrome oxidase I sequences from 242 butterflies (615 bp) and 66 attendant ants (585 bp) from 22 populations was carried out to explore the relationship between ant association and butterfly population structure. This analysis revealed 12 closely related butterfly haplotypes in three distinct clades roughly correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 53 publications
(50 reference statements)
2
8
0
1
Order By: Relevance
“…This in turn could explain the higher host plant diversity for Theclinae that was found in this study and previous studies [14], [74]–[76], and may also explain the species diversity in other subfamilies in the Lycaenidae and Riodinidae [77]. Recently, Megens et al [78] suggested that the timing of a basal radiation in Arhopala (the most speciose genus of Theclinae, with 9% of the species in Southeast Asia) coincided with major climate changes commencing during the middle Miocene.…”
Section: Discussionsupporting
confidence: 68%
“…This in turn could explain the higher host plant diversity for Theclinae that was found in this study and previous studies [14], [74]–[76], and may also explain the species diversity in other subfamilies in the Lycaenidae and Riodinidae [77]. Recently, Megens et al [78] suggested that the timing of a basal radiation in Arhopala (the most speciose genus of Theclinae, with 9% of the species in Southeast Asia) coincided with major climate changes commencing during the middle Miocene.…”
Section: Discussionsupporting
confidence: 68%
“…These sequences were supplemented by 385 further sequences of Lycaenidae deposited in GenBank as of March, 2006 (Table 5). They include sequences from further studies on Agrodiaetus [29,44], the Palaearctic genus Maculinea [54], Nearctic Lycaeides melissa [55], the Oriental genus Arhopala [46,50], the Australian genera Acrodipsas [56] and Jalmenus [57], and the South African Chrysoritis [58] as well as a few sequences which have only been used as outgroups in non-Lycaenidae studies (e.g. [59,60]).…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, the role of mutualistic interactions in evolutionary diversification has been less explored [5,6]. Butterflies in the families Lycaenidae and Riodinidae have been a focal point for interest in the connection between diversification and mutualistic interaction [7][8][9][10]. Approximately, one third of all butterfly species are lycaenids, and more than half of all lycaenids are myrmecophilous: they engage in interactions with ants that are either mutualistic, commensalistic or parasitic [11].…”
Section: Introductionmentioning
confidence: 99%